2021
DOI: 10.17645/pag.v9i2.3938
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Input Rules and Ballot Options on Voting Error: An Experimental Analysis

Abstract: When election reforms such as Ranked Choice Voting or the Alternative Vote are proposed to replace plurality voting, they offer lengthier instructions, more opportunities for political expression, and more opportunities for mistakes on the ballot. Observational studies of voting error rely on ecological inference from geographically aggregated data. Here we use an experimental approach instead, to examine the effect of two different ballot conditions at the individual level of analysis: the input rules that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…One of the most important elements of this study was the errors that were observed. On RCV ballots, error can be categorized into “mismarked” and “void” ballots (Maloy & Ward, 2021). Mismarked ballots are those which have errors, such as selecting the wrong candidate, but the ballot is still able to be counted in the final tally.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most important elements of this study was the errors that were observed. On RCV ballots, error can be categorized into “mismarked” and “void” ballots (Maloy & Ward, 2021). Mismarked ballots are those which have errors, such as selecting the wrong candidate, but the ballot is still able to be counted in the final tally.…”
Section: Resultsmentioning
confidence: 99%
“…Voting time is not the only consideration. Errors play a critical role in determining the overall usability of ballots – described previously as mismarked or void (Maloy & Ward, 2021). While void errors are critical, it is equally important to note that mismarked errors may result in a ballot that is unreflective of the voter’s intent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation